Sustainability Issues of Business Security in Ukraine: Risk Factors of the Corporate Criminal Liability - Datsiuk, Vitalii; Nesterova, Iryna (Teisė, 2020)
The article deals with recent changes in the Ukrainian criminal legislation, which concerns the activities of the criminal-legal character introduction against legal persons (quasi-corporate criminal liability) in the context of risk factors for sustainable business development.
Keywords: business security; corporate criminal liability; corporate social responsibility; crime; risk factors; sustainability of business